Pengaruh Self Control Financial Dan Love Of Money Terhadap Financial Management Behavior Generasi Z - Mujiyanti, Nur Mujiyanti; Nailah, Syafira Khansa; Aristawati, Nadiyah; Octaviani, Jessica Erviana; Linawati, Linawati (Jurnal Portofolio : Jurnal Manajemen dan Bisnis, 2025)
This study aims to analyze the influence of Self-Control Financial and Love of Money on Financial Management Behavior among Generation Z in South Jakarta. A quantitative approach was employed using multiple linear regression analysis. The sample consisted of 100 respondents selected through purposive sampling, with criteria including individuals aged 18–28 years who actively manage their personal finances. The results indicate that Self-Control Financial has a positive and significant effect on Financial Management Behavior. Love of Money also shows a positive and significant influence on individuals’ financial management practices. This study contributes to the existing literature by providing empirical evidence on the role of psychological factors in shaping financial behavior among digital-native youth, and it offers practical implications for developing more effective financial education strategies in the digital era.